Annually Verified Growth of Cedrela Fissilis from Central Brazil. Issue 4 (6th June 2019) - Hammerschlag, Izabela; Macario, Kita D; Barbosa, Ana Carolina; Pereira, Gabriel de Assis; Farrapo, Camila Laís; Cruz, Francisco
ABSTRACT: Given the difficulty in obtaining robust chronologies from tree rings in tropical regions, the search for appropriate species is very important. Both dendrochronology and radiocarbon ( 14 C) measurements are required to validate the use of any specific tree. Some species have proved to be reliable for representing atmospheric 14 C concentration over time, such as Cedrela fissilis and Araucaria angustifolia . However, not only the species have to be validated, but also different climatic conditions may result in different growth patterns for the same species. In this work, we study the annual growth rings of Cedrela fissilis from a dry tropical forest patch typical of a highly seasonal climate in central Brazil. 14 C accelerator mass spectrometry (AMS) was used to compare the isotopic ratios of tree rings with the 14 C concentrations in the atmosphere during the nuclear tests based on curve Bomb13SH 1-2. Results are similar to the bomb peak curve within the period from 1958 to 1980 AD and serve as a crucial test for the cross-dating analyses using the skeleton plot technique.